The organum vasculosum of the lamina terminalis and subfornical organ: regulation of thirst - Wang, Jiaxu; Lv, Fenglin; Yin, Wei; Gao, Zhanpeng; Liu, Hongyu; Wang, Zhen; Sun, Jinhao (Frontiers in Neuroscience, 2023)
Thirst and water intake are regulated by the organum vasculosum of the lamina terminalis (OVLT) and subfornical organ (SFO), located around the anteroventral third ventricle, which plays a critical role in sensing dynamic changes in sodium and water balance in body fluids. Meanwhile, neural circuits involved in thirst regulation and intracellular mechanisms underlying the osmosensitive function of OVLT and SFO are reviewed. Having specific Nax channels in the glial cells and other channels (such as TRPV1 and TRPV4), the OVLT and SFO detect the increased Na+ concentration or hyperosmolality to orchestrate osmotic stimuli to the insular and cingulate cortex to evoke thirst. Meanwhile, the osmotic stimuli are relayed to the supraoptic nucleus (SON) and paraventricular nucleus of the hypothalamus (PVN) via direct neural projections or the median preoptic nucleus (MnPO) to promote the secretion of vasopressin which plays a vital role in the regulation of body fluid homeostasis. Importantly, the vital role of OVLT in sleep-arousal regulation is discussed, where vasopressin is proposed as the mediator in the regulation when OVLT senses osmotic stimuli.